Best practices for community-engaged participatory research with Pacific Islander communities in the USA and USAPI: protocol for a scoping review. Issue 1 (24th January 2018) - McElfish, Pearl Anna; Ayers, Britni L; Purvis, Rachel S; Long, Christopher R; Sinclair, Ka'imi; Esquivel, Monica; Steelman, Susan C
Abstract : Introduction: Community-based participatory research is a partnership approach to research that seeks to equally involve community members, organisational representatives and academic partners throughout the research process in a coequal and mutually beneficial partnership. To date, no published article has synthesised the best practices for community-based participatory research practices with Pacific Islanders. Methods and analysis: The reviewers will examine studies' titles, abstracts and full text, comparing eligibility to address discrepancies. For each eligible study, data extraction will be executed by two reviewers and one confirmation coder, comparing extracted data to address any discrepancies. Eligible data will be synthesised and reported in a narrative review assessing coverage and gaps in existing literature related to community-based participatory research with Pacific Islanders. Discussion and dissemination: The purpose of this review is to identify best practices used when conducting community-based participatory research with Pacific Islanders; it will also extrapolate where the gaps are in the existing literature. This will be the first scoping review on community-based participatory research with Pacific Islanders. To facilitate dissemination, the results of this scoping review will be submitted for publication to a peer-reviewed journal, presented at conferences and shared with community-based participatory research stakeholders.